(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The shape and size of a skull provides insight into the age, breed and gender of the animal. Skull shape variations have been reported in different animals, with some theories linking these variations to evolution and/or migration. This study assessed the variations observed in the skull shape, size and gross morphometrics of two groups of the Eidolon helvum obtained from two geographical regions in Nigeria (south and north). All skulls were rostro-caudally elongated, having a dolichocephalic appearance. The skulls from the north had a distinct dome shape, with a more prominent zygomatic process, absence of a ‘diastema’ and an extra upper molar, while the southern skulls showed a more dorsally flattened skull and a less prominent zygomatic process. The shape of the sagittal crest was different in the two groups, while there was the presence of an accessory infraorbital foramen in some of the southern skulls. The southern skulls lacked the palatine foramen. The lacrimal foramen was observed to be more caudally placed in the southern skulls. Values for most linear measurements were higher in the northern skulls, although statistically significant difference was not present in all. The value for the neurocranial volume was considerably higher in the northern skulls (4.41 ± 0.28 mls) relative to the southern skulls (2.0 ± 0.27 mls). Statistically significant differences were not observed between males and females (within regions). Data obtained from this study may find application in evolution and migration studies, wildlife medicine and surgery and comparative and forensic anatomy.